Framing food systems transformation: A diagnostic framework and checklist for integrating transformative actions into African food systems - Neely, Constance; Chesterman, Sabrina; Chevallier, Romy; Getz Escudero, Arthur; Thornton, Philip K.; Mutamba, Manyewu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report forms part of an AICCRA knowledge series on Food Systems. This report presents a diagnostic framework and checklist for integrating transformative actions into African food systems.